A Pilot Study of the Efficacy of a Computerized Executive Functioning Remediation Training With Game Elements for Children With ADHD in an Outpatient Setting: Outcome on Parent- and Teacher-Rated Executive Functioning and ADHD Behavior. (November 2014) - van der Oord, S.; Ponsioen, A. J.G. B.; Geurts, H. M.; Brink, E. L. Ten; Prins, P. J. M.
Objective: This pilot study tested the short- and long-term efficacy (9 weeks follow-up) of an executive functioning (EF) remediation training with game elements for children with ADHD in an outpatient clinical setting, using a randomized controlled wait-list design. Furthermore, in a subsample, that is, those treated with methylphenidate, additive effects of the EF training were assessed.Method: A total of 40 children (aged 8-12 years) were randomized to the EF training or wait-list. The training consisted of a 25-session training of inhibition, cognitive flexibility, and working memory. Treatment outcome was assessed by parent- and teacher-rated EF, ADHD, oppositional deviant disorder, and conduct disorder symptoms.Results: Children in the EF training showed significantly more improvement than those in the wait-list condition on parent-rated EF and ADHD behavior in the total sample and in the subsample treated with methylphenidate. Effects were maintained at follow-up.Conclusion: This pilot study shows promising evidence for the efficacy of an EF training with game elements.